ZONAL LABELING OF EDGE COMB PRODUCT OF GRAPHS - Soewongsono, Junita Christine; Putra, Ganesha Lapenangga; Ariyanto, Ariyanto; Pangaribuan, Rapmaida Megawaty (Jurnal Matematika UNAND, 2024)
Given a plane graph $G=(V,E)$. A zonal labeling of graph $G$ is defined as an assignment of the two nonzero elements of the ring $\mathbb{Z}_3$, which are $1$ and $2$, to the vertices of $G$ such that the sum of the labels of the vertices on the border of each region of the graph is $0\in\mathbb{Z}_3$. A graph $G$ that possess such a labeling is termed as zonal graph. This paper will characterize edge comb product graphs that are zonal. The results show that $P_m\trianglerighteq_eC_n$, $C_n\trianglerighteq_e C_r$, $S_p\trianglerighteq_e C_n$, and $S_p\trianglerighteq_e F_t$ are zonal in some cases, but not in others.